Rancang Bangun Perangkat Wearable "Clever-Mask" untuk Pemantauan Pola Pernapasan sebagai Penanganan Pertama pada Pasien Terdampak Covid-19 secara Kontinyu - Moch. Alvin Yasyfa Salsabil; Dahnial Syauqy; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Big Pandemic Covid-19, In â€‹â€‹Indonesia Deaths due to the Covid-19 virus up to 144,000 thousand people. One of the causes of the high number of deaths due to Covid-19 cases is the lack of prompt treatment for patients affected by Covid-19 in the cytokine storm phase. Cytokine Storm is a condition in which the release of mal-adaptive cytokines is â€œout of controlâ€ in response to infection and stimuli. Cytokine storms attack lung tissue and blood vessels. In this study, a system consisting of several components was used, namely, Arduino Mega 2560 Rev 3 as a microcontroller board, NTC Thermistor Sensor as a breathing signal generator mounted on an oxygen mask and an OLED display to display the output in the form of "Normal" or "Abnormal". This system uses the Min, Max, Amplitude, Interval and Breath Rate features per 4 cycles of 4 cycles which are then classified using the Support Vector Machine. In system testing related to testing the accuracy of the classification results using the Support Vector Machine, it was carried out 12 times to find the class of the test data obtained and the accuracy level of the classification results with SVM was 91.66. In the computational testing of the system, the classification was carried out 12 times to get the class classification results from the test data and the average computation time was 29.29 ms.